Respuestas

2013-06-18T23:23:15+02:00
 y =  ex3 + x3                                      formula ( ex3= u x dv + v x du
                                                              e.dx3+x3.de

                                                          e3^2 +3x
                                                             

                                                                x3=   x elevado a la n

n                                                                   3xelevad2


y =  ex3 + x3
y´= e3x^2 +3x +3x^2